Admission Pattern and Outcome of Patients Admitted to Pediatric Intensive Care Unit, CMH, DHAKA: 2-Years Study (Journal of Comilla Medical College Teachers' Association, 2024)
Background: The care of critically ill children remains one of the most demanding and challenging aspects in the field of pediatrics. The main purpose of the pediatric intensive care unit (PICU) is to prevent mortality of these children by intensive monitoring, early intervention and quality care with an objective to achieve better prognosis than the patients admitted in other parts of the hospital. Pediatric intensive care is an emerging concept in Bangladesh with only a few PICUs mostly in the capital city, Dhaka. This study was conducted to find out the pattern of diseases and outcome at our centre which would help in better understanding, modifying practices if necessary, leading to better management and outcome and necessary resource allocation by the planners.Methods: It was a descriptive study conducted over 2 years, from October 2018 to September 2020, including all patients admitted to PICU of Combined Military Hospital, Dhaka. Bangladesh. Total 730 patients were admitted during the study period. Data were extracted from the patient’s files including demographic and clinical characteristics, previously diagnosed chronic conditions and outcome including length of stay (LOS) or death were noted.Results: Total 730 patients were admitted during the study period. Mean age of the patient was 4 months and 4.68 days and mean hospital stay was 4.37±0.5 days. Preschool children (1–5 years of age) were the largest age group (n = 313). November and December were the most common months of admission (n = 58 and 57, respectively). Total 658 (90.1%) patient were improved and discharged, 32 (4.4%) patients were referred to surgical department, 3 (0.4%) patients was discharged against medical advice (DAMA) whereas, unfortunately 37 (5%) patients died. Central nervous system was involved in 198 (27.1%) and skin was the least involved system. A higher portion of patient of Preschool (1-5yrs) 15 (4.8%) died compared to 5 years but the relationship was not significant statistically (p = 0.101). A higher proportion of males, 23 (5.2%), died compared to females, 14 (5%). This relationship was not statistically significant (p = 0.706). A higher proportion of death also observed in LOS< 24 hours, but the relationship was not significant (p=0.168).Conclusion: This study revealed that neurological, genetic defect and respiratory diseases were the major causes of admission into the PICU with survival rate of 95%. A PICU is an essential part of hospital caring for the critically ill child by reducing morbidity and mortality. An effective and wellequipped PICU with modern facilitates can bring out the desirable outcome.  J Com Med Col Teachers’ Asso July 2023; 27(2): 62-66